The translation of noun from non-English to English: a systematic literature review / Shang Xiaoyan, Teh Hong Siok and Nur Huslinda Che Mat - Shang, Xiaoyan; Teh, Hong Siok; Che Mat, Nur Huslinda (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
Linguistic structures and cultural variations pose significant challenges in the field of translation studies. Understanding the translation of nouns is essential for bridging linguistic gaps and enhancing cross-cultural communication. However, there have been limited systematic reviews on the issue. This study aims to systematically review and analyze the existing literature on the translation of nouns from non-English language to English as a target language. In accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, a systematic review was conducted utilizing two primary databases, Web of Science and Scopus. The process comprised three main stages: keyword identification, article screening, and final article determination. Primary searches from 2013 to 2023 revealed 1418 studies on the topic under investigation. After scrutinizing abstracts and eliminating duplicates, 16 studies were selected for further analysis. A thematic analysis was conducted to derive themes for the translation of nouns in these studies. The themes of the translation of nouns from non-English to English that emerged were: (1) the features of nouns; (2) linguistic scope; (3) the machine translation (MT) system; (4) hindrances in translation; (5) translation strategies. These five themes were further categorized into 20 sub-themes. The results provide linguists and translators with an in-depth overview of the published research on noun translation from other languages into English, the target language. This overview paves the way for the development of more efficient translation approaches. This systematic review enriches the field of noun translation from non-English to English, providing a robust foundation for future research. Given the limited number of existing studies on noun translation, there is a significant need for further investigation to explore this area more thoroughly. Future research initiatives should further scrutinize the challenges and strategies associated with noun translation, contributing to a more detailed understanding of this linguistic domain.